Pengaruh viral marketing dan celebrity endorsement terhadap keputusan pembelian melalui kepercayaan konsumen sebagai variabel intervening (Studi pada Konsumen Glad2Glow di TikTok Daerah Istimewa Yogyakarta) - Misbahul Anwar; Kartika Anggraeni (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze the influence of Viral Marketing and celebrity endorsements on purchasing decisions through consumer trust as an intervening variable for Glad2Glow products on TikTok. The subjects were Glad2Glow consumers in the Special Region of Yogyakarta who have TikTok accounts and have purchased Glad2Glow products. This quantitative study used primary data with a sample size of 170 respondents using a purposive sampling technique. The data analysis technique used in this study was Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0 software. Based on the results of the data analysis, the results showed that Viral Marketing had a positive and significant effect on consumer trust, celebrity endorsements had a positive and significant effect on consumer trust, Viral Marketing had a positive but insignificant effect on purchasing decisions, celebrity endorsements had a positive and significant effect on purchasing decisions, consumer trust had a positive and significant effect on purchasing decisions, consumer trust was able to mediate the influence of Viral Marketing on purchasing decisions, and consumer trust was able to mediate celebrity endorsements on purchasing decisions.